KRITIK JUBRAN KHALIL JUBRAN TERHADAP KONSTRUKSI AGAMA DALAM CERPEN “KHALĪL AL-KĀFIR” - Nurain, Nurain (Sunan Kalijaga State Islamic University Yogyakarta, 2018)
The material object of this paper is a short story written by Jubran Khalil Jubran, entitled Khalīl al-Kāfir. The formal object is Jubran's criticism of religious construction from the transcendentalist perspective. It aims to answer the question why Jubran criticized religious construction in his writing. As a migrant Arabic writer, who has the experiences of living in the Western and Eastern world, Jubran is able to critically read the construction of religion in the Christian tradition. His criticism is expressed in Khalīl al-Kāfir, which tells his protest and rebellion against the religious leaders as well as the exclusivity and formality of religion which eliminate its spiritual dimension as the soul of human mental enlightenment. The analysis shows that Jubran criticized the sacred authority of priests and monks because of his views that God is immanent and existent everywhere. The immanence of God implies that He is being a power in every human soul. Meanwhile, His existence everywhere emphasizes the over-soul of God's oneness with humans and nature, the oneness of God with all creatures in the universe.